2018
DOI: 10.1371/journal.pone.0195023
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage cocktail for biocontrol of Escherichia coli O157:H7: Stability and potential allergenicity study

Abstract: Escherichia coli O157:H7 has become a global public health and a food safety problem. Despite the implementation of control strategies that guarantee the safety in various products, outbreaks persist and new alternatives are necessary to reduce this pathogen along the food chain. Recently, our group isolated and characterised lytic bacteriophages against E. coli O157:H7 with potential to be used as biocontrol agents in food. To this end, phages need certain requirements to allow their manufacture and applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 49 publications
5
32
0
Order By: Relevance
“…Taken together, the results of the pH-inactivation assay suggested that VR26 sustained its lytic property through a broad range of pHs, indicating greater stability of this phage compared with other O26:H11-infecting [ 24 ] or even O157:H7-infecting viruses [ 24 , 35 , 36 , 37 ] described in previous studies.…”
Section: Resultssupporting
confidence: 64%
“…Taken together, the results of the pH-inactivation assay suggested that VR26 sustained its lytic property through a broad range of pHs, indicating greater stability of this phage compared with other O26:H11-infecting [ 24 ] or even O157:H7-infecting viruses [ 24 , 35 , 36 , 37 ] described in previous studies.…”
Section: Resultssupporting
confidence: 64%
“…Oral administration of different anti- Salmonella bacteriophage mixtures into mice did not result in gross clinical changes or mortality [12, 28]. Additionally, mice treated with a bacteriophage therapeutic against E.coli also did not exhibit any toxic effects [29].…”
Section: Discussionmentioning
confidence: 99%
“…The pH stability was tested with 10 μL phage suspension in 990 μL SM buffer solutions adjusted to pH 2, 3, 4, 5, 7, 10, 11, and 12 overnight. Stability of phage under UV radiation was tested according to a previous report [ 44 ] with a modification. Briefly, 1 mL of phage lysate (10 8 PFU ml −1 ) was added into the 24-well plate and then irradiated for 0, 15, 30, 45 and 60 min with the UV light (λ = 365 nm; 320 mW/m 2 ).…”
Section: Methodsmentioning
confidence: 99%